Active tectonics evaluation from geomorphic indices for the central and the southern Longmenshan range on the Eastern Tibetan Plateau, China. Issue 8 (11th August 2016) - Gao, Mingxing; Zeilinger, Gerold; Xu, Xiwei; Tan, Xibin; Wang, Qingliang; Hao, Ming
Abstract: We applied the geomorphic indices (hypsometry and stream length gradient) to evaluate the differential uplift of the central and southern Longmenshan, a mountain range characterized by rapid erosion, strong tectonic uplift, and devastating seismic hazards. The results of the geomorphic analysis indicate that the Beichuan‐Yingxiu fault and the Shuangshi‐Dachuan fault act as major tectonic boundaries separating areas experiencing rapid uplift from slow uplift. The results of the geomorphic analysis also suggest that the Beichuan‐Yingxiu fault is the most active fault with the largest relative uplift rates compared to the rest of the faults in the Longmenshan fault system. We compared reflected relative uplift rates based on the hypsometry and stream length gradient indices with geological/geodetic absolute rates. Along‐strike and across‐strike variations in the hypsometry and stream length gradient correlate with the spatial patterns derived from the apatite fission track exhumation rates, the leveling‐derived uplift rate, and coseismic vertical displacements during the 2008 Wenchuan earthquake. These data defined multiple fault relationships in a complex thrust zone and provided geomorphic evidence to evaluate the potential seismic hazards of the southern Longmenshan range. Key Points: The Beichuan‐Yingxiu fault is identified as the most active fault with the largest relative uplift rate in the Longmenshan range The Beichuan‐Yingxiu and the Shuangshi‐Dachuan faults act as the main tectonic boundaries of the Longmenshan range Uplift at different timescales is consistent in the Longmenshan range